Vitamin D deficiency: how prevalent it is? - Pallewad, Irwant V.; Upadhye, Jayshree J. (International Journal of Research in Orthopaedics, 2019)
Background: Vitamin D deficiency is frequently seen nowadays due to inadequate exposure to sun and pollution. The present study was undertaken to evaluate the prevalence of vitamin D deficiency in patients presenting with suggestive complaints. Methods: The present study is a retrospective study done at Srinivas Institute of Medical Sciences and Research Centre, Mukka, Suratkal, Mangaluru. Patients who have musculoskeletal or other problem suggestive of vitamin D deficiency were advised vitamin D levels. We went through OPD papers of only those patients with reports of Vitamin D levels. Results: In present study, out of 100 patients, 42 (42%) patients had normal BMI, 23 (23%) patients were overweight, 24 (24%) patients were obese while 11 (11%) patients were underweight. 46 (46%) patients were having walk for exercise purpose, 21 (21%) were doing work out at gym while 33 (33%) patients were walking only for doing some work. 47 (47%) patients had normal levels of vitamin D, 31 (31%) had insufficient levels while 22 (22%) patients had deficient levels of vitamin D. So, prevalence of vitamin D deficiency was 22% and for vitamin D insufficiency was 31%. Conclusions: In present study, we conclude that irrespective of normal body mass index or physical activity, patients presented with various complaints. In them, vitamin D levels were either insufficient or deficient in large number of patients. So, vitamin D levels should be done as screening or at least when patients present with suggestive complaint.